Knowledge, and attitude towards human papilloma virus infection among pharmacy students in Mumbai, India - Limaye, Dnyanesh; Mehta, Drashty; Singh, Shakshi; Pardeshi, Apurva; Patil, Tanvi; Sydymanov, Arlan; Limaye, Vaidehi; Pitani, Ravi Shankar; Sathe, Sushama; Kapadi, Atul; Fortwengel, Gerhard (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Human papillomavirus (HPV) is a common sexually transmitted infection (STI) that may cause cervical cancer and other malignancies including those of the vulva, anus, vagina, penis, head and neck. In most Asian countries including India, cervical cancer is the second most common cancer in women. Awareness about HPV and cervical cancer, use of vaccines can be very helpful in prevention, control and early diagnosis of cervical cancer. Methods: A cross-sectional study was carried out among students from Mumbai University, India during May - June 2017. Two hundred students were approached to participate in the study of which 142 were selected to participate (males: 54; females: 88). Pretested questionnaire was distributed and collected data was analyzed using IBM SPSS version 23. Results: Participants had fair knowledge (61% average) about HPV, whereas knowledge about symptoms, prevention and spread of HPV was very poor i.e. 18%. Knowledge about HPV vaccine was 50% and 78% participants had positive attitude for HPV vaccine. Conclusions: This study showed the lacunas in the pharmacy curriculum and urgent need to create awareness of HPV among bachelor of pharmacy students from Mumbai University.